The Influence of Corporate Governance, Financial Performance, and Financial Statement Quality on Company Value in the Manufacturing Sector in Indonesia (Empirical Study on Food and Beverage Companies Listed on the IDX for the Period 2022–2024) - Alfonsiana Desi Ratna; Retno Kurnianingsih (Universitas KH. Abdul Chalim Mojokerto, 2026)
A study on the influence of corporate governance, financial performance, and the quality of financial statements on the value of the company. This research is included in the category of quantitative research. The population that is the object of the study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. The sampling method used is purposive sampling, which is sampling with specific considerations. The variables studied include governance, financial performance, and quality of financial statements as variable X and company value as variable Y. The analysis tool used in this study is SPSS. The findings of this study show that corporate governance, financial performance, and the quality of financial statements have a partial and simultaneous positive and significant influence on the value of the company, in food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2022-2024 period.